Effect of PEG and CMC on Papaya (Carica papaya L.) Extract Against Aedes aegypti Larvae - Rochmadina Suci Bestari; Fidhia Nur Rif'aini; Riandini Aisyah; Listiana Masyita Dewi; Devi Usdiana Rosyidah; Retno Sintowati; Hidayah Karuniawati (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Dengue haemorrhagic fever (DHF) cases are still high in America and Asia region, including Indonesia. Eradication of DHF can be done by larvacide. Temephos 1%, chemical larvacide used in Indonesia for decades, can cause environment degradation and allergic reaction in human. Papaya stem extract as biolarvacide contains saponins, tannins, alkaloids, flavonoids, papain and essential oils which have larvicidal activity. It can be applicable in all over the world. This study was conducted to determine the better suspending agent between CMC or PEG of papaya stem extract to kill Aedes aegypti larvae. Objective: To determine the better suspending agent to kill Aedes aegypti larvae. Method: This study was true experimental study in laboratory, used post-test only controlled group design. This study used samples consist of Aedes aegypti instar III-IV larvae. There were seven experimental groups, consist of positive control group, negative control group for CMC, negative control group for PEG, extract concentration of 1.5% with CMC suspending agent, extract concentration of 1.5% with PEG suspending agent, extract concentration of 2% with CMC suspending agent, extract concentration of 2% with PEG suspending agent. Each group was repeated 4 times and counted every 6 hours (6th, 12th, 18th, 24th). Data analysis using the SPSS application ver 23. Probit test used to determine the effectiveness of the larvacide, LC50 and LT50 to determine the concentration and time to kill 50% of Aedes aegypti larvae. It used Kruskal Wallis Test to compare four dependent groups. It used Mann Whitney Test to compare the differences of each group. Result: The study showed that LC50 PEG was 0.033%, LC50 CMC was 0.321%, LT50 (PEG+1.5%) was 20.8 hours, LT50 (PEG+2%) was 30.7 hours, LT50 (CMC+1.5%) was 23.5 hours, LT50 (CMC+2%) was 40.7 hours. Based on the probit test, the LC50 and LT50 results showed that papaya stem methanol extract with PEG suspending agent was more effective than CMC suspending agent, it needed lower concentration and lower time to kill 50% of larvae. Kruskall Wallis Test result p<0.05, so there was significantly difference between groups. Post hoc Mann-Whitney Test result p<0.05 between C(-) PEG group with P1, P2, P3, P4 and between C(-) CMC group with P1, P2, P3, P4, so there was significantly difference between C(-) PEG with each group and C(-) CMC with each group. Conclusion: It can be concluded that papaya stem methanol extract with PEG suspending agent was more effective than CMC suspending agent to kill Aedes aegypti larvae.